Role of cytokines and platelet-activating factor in inflammatory bowel disease - Nassif, Anis (1996)
BACKGROUND: Platelet-activating factor (PAF) and cytokines, such as interleukins, tumor necrosis factor, and others, are thought to play a role in the inflammatory process involving gastrointestinal disorders such as Crohn's disease, ulcerative colitis, ischemic colitis, or antibiotic-associated colitis. PURPOSE: This study was undertaken to review the latest literature on the role of PAF and cytokines in the genesis of inflammatory bowel disease and implications for therapy and management. RESULTS: PAF is an endogenous phospholipid involved in hypersensitivity and inflammatory reactions such as platelet and neutrophil aggregation, vasodilation, increased vascular permeability, and leukocyte adhesion, which have been associated with inflammatory processes. Cytokines are peptides that regulate and coordinate inflammatory and immunologic responses. Increased production of cytokines has been reported during Crohn's disease and ulcerative colitis and is correlated with disease activity. CONCLUSIONS: Because PAF and cytokines may have an important role in the pathogenesis of inflammatory bowel disease, their inhibition by specific antagonists, mediators, or other agents such as steroids may have a potential therapeutic benefit in treatment and management of these inflammatory diseases in the near future.